2021
DOI: 10.21608/msnj.2022.113636.1015
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Guidelines and its Effect on Reducing Central Line Related Infection among Traumatic Patients

Abstract: Background: Central venous catheter is required in multiply injured patients either in the initial resuscitation phase or during an intensive care unit stay. There are potential complications associated with central line access as infection. Nurses play a crucial role in preventing this infection. Aim of the study: To evaluate the effect of nursing guidelines on reducing central line related infection among traumatic patients. Design: A quasi-experimental research design. Sample: A purposive sample of 60 newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…In the current study, more than half of nurses were from urban areas. This agreed with Abdel Ghafour et al (2021), who found that more than half of the nurses were from urban areas Regarding to level of education of the studied nurses, the current study result clarified that two fifths of them had a nursing school diploma; this might due to the highly qualified nurses always perform administrative work. In congruence with these findings, Moursy and Sharaf (2017) who study about "vascular access care at hemodialysis unit; nurses' compliance to infection prevention and control practice" and reported that highly percentage of the studied nurses the educational level were diploma.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, more than half of nurses were from urban areas. This agreed with Abdel Ghafour et al (2021), who found that more than half of the nurses were from urban areas Regarding to level of education of the studied nurses, the current study result clarified that two fifths of them had a nursing school diploma; this might due to the highly qualified nurses always perform administrative work. In congruence with these findings, Moursy and Sharaf (2017) who study about "vascular access care at hemodialysis unit; nurses' compliance to infection prevention and control practice" and reported that highly percentage of the studied nurses the educational level were diploma.…”
Section: Discussionsupporting
confidence: 90%